Administration and Monitoring Burden of High-Efficacy Disease-Modifying Therapies for Multiple Sclerosis: A Delphi Consensus of Clinical Experts from Saudi Arabia - Seraj Makkawi; Ahmad Abulaban; Yaser Al Malik; Ebtesam Alshehri; Ahmed Althobaiti; Salman Aljarallah; Ahmed Elboghdady; Lynn AlHajjar; Sahar Shami; Saeed Bohlega; Mohammed Aljumah (Neurology and Therapy)
Abstract Introduction The emergence of high-efficacy disease-modifying therapies (HE DMT) for multiple sclerosis (MS) may pose challenges to the administration and monitoring burden of the therapies. This article presents the results of the Delphi consensus method to generate insights from experts on the administration and monitoring burden of HE DMT in Saudi Arabia with a special focus on cladribine. Methods Between January and March 2023, a two-round modified Delphi method was used to establish consensus regarding the administration and monitoring burden of HE DMTs used for MS. Through a questionnaire, the advisors evaluated 17 properties of six individual HE DMTs on the basis of their clinical experience. Advisors were required to rank each property on a scale of 1–5, with 1 being the lowest burden and 5 being the highest burden. Results Experts ranked cladribine as having the lowest monitoring burden, followed by ofatumumab and ocrelizumab. Natalizumab and fingolimod were ranked fourth, and alemtuzumab had the highest burden. During the first round, experts agreed on the scores of the administration burden properties, except for hospital visit time and facility use during administration for ofatumumab, route of administration for fingolimod, monitoring of specific side effects and frequency of lab tests at follow-up, and the washout period for natalizumab. During the second round, there was agreement on all properties. Conclusion In the absence of alternative scientific data, recommendations from experts and their consensus provide useful insights into the administration and monitoring burden of HE DMTs used for MS in Saudi Arabia.